Antioxidant low-temperature conductive paste and preparation method thereof

By modifying the surface of the copper powder, uniformly covering the graphene layer to form graphene-coated copper powder, the existing low-temperature conductive paste has solved the problems of high cost and insufficient conductivity and stability, and achieved high conductivity and stability and reduces curing costs.

CN119446622AInactive Publication Date: 2025-02-14西安宏星电子浆料科技股份有限公司

Patent Information

Application Number
CN202510039666.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-02-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing low-temperature conductive paste has high cost, insufficient conductivity and stability, which limits its application scope.

Method used

By modifying the surface of the copper powder, the graphene layer is uniformly coated to form graphene-coated copper powder, the contact area between conductive particles is increased, and the copper powder oxidation is prevented through the graphene coating.

Benefits of technology

It improves the conductivity and stability of conductive materials, reduces curing costs, and expands the scope of application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119446622A_ABST
    Figure CN119446622A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of conductive materials, and particularly relates to antioxidant low-temperature conductive paste and a preparation method thereof. The conductive powder comprises copper powder modified by a surfactant and a graphene coating layer coated on the surface of the copper powder modified by the surfactant. The conductive paste provided by the invention comprises the conductive powder provided by the invention. Compared with traditional conductive copper paste, the conductive paste is more stable. On one hand, the surface of the copper powder is modified, so that the surfaces of copper powder particles are coated with graphene more uniformly, continuous contact is formed among the conductive particles, the contact area is increased, and the conductivity of the whole conductive material is increased; and on the other hand, the surface of the copper powder in the conductive slurry is coated with the graphene, so that the copper powder can be prevented from being oxidized, the sintering and curing condition can be changed from a protective atmosphere to an air atmosphere, the cost is further reduced, and the application range of the conductive slurry is expanded.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of conductive materials, and in particular relates to an anti-oxidation low-temperature conductive slurry and a preparation method thereof. Background Art

[0002] Low temperature conductive paste, including silver paste and copper paste, has good conductivity after curing under certain conditions, and the resistivity can reach 10 -5 Ω·cm, but the actual cost of use is relatively high. In addition, silver itself has defects such as silver migration and sulfidation; copper paste will produce an oxide layer that makes the conductivity unstable, and needs to be sintered and solidified in a protective atmosphere, which further limits the application scope of copper paste. With the development of electronic technology, new technologies and products have put forward higher requirements on the performance of conductive copper paste. Improving performance and reducing costs are the goals that conductive materials are constantly pursuing.

[0003] Single-layer graphene is a two-dimensional crystalline material composed of carbon atoms. 2 The hybrid honeycomb structure of the planar film can achieve an electron mobility of 15000cm 2 / (vs), and its resistivity reaches 10 -6 Ω·cm, is the material with the lowest resistivity in the world. The high conductivity, stability and nano-layer structure of graphene determine that graphene can be used as a high-performance conductive material.

[0004] The cost of using graphene alone as a conductive material is too high, and the application scope of using conductive copper paste alone is limited. Therefore, the art urgently needs a conductive paste with low cost, high conductivity and high stability. Summary of the invention

[0005] In view of this, the present invention provides a conductive paste with low cost, good conductivity and good anti-oxidation performance.

[0006] A first aspect of the present invention provides a conductive powder, comprising copper powder modified by a surfactant and a graphene coating layer coated on the surface of the copper powder modified by the surfactant.

[0007] In one or more embodiments, the average particle size of the copper powder is ≤ 8 μm.

[0008] In one or more embodiments, the surfactant is selected from one or more of disodium ethylenediaminetetraacetate, sodium lauryl sulfate, cetyltrimethylammonium bromide, and sodium dodecylbenzene sulfonate.

[0009] In one or more embodiments, in the surfactant-modified copper powder, the non-polar end of the surfactant is adsorbed on the copper powder.

[0010] In one or more embodiments, the graphene sheet has a diameter of 1-3 μm.

[0011] In one or more embodiments, the graphene coating has a thickness of less than 10 nm.

[0012] In one or more embodiments, the coverage of the graphene coating layer on the surface of the surfactant-modified copper powder is 90-100%.

[0013] In one or more embodiments, in the conductive powder, the mass fraction of the graphene coating layer is 1-2%.

[0014] The second aspect of the present invention provides a method for preparing the conductive powder according to the first aspect of the present invention, the method comprising the steps of: a. treating the copper powder with a reducing agent to obtain the copper powder with the oxide layer removed; b. adding the copper powder with the oxide layer removed into an aqueous solution containing a surfactant, stirring, separating to obtain a solid, and drying the solid to obtain the copper powder modified by the surfactant; c. Adding the copper powder modified by the surfactant into the liquid containing graphene, stirring until floccules appear, and then standing to separate the floccules and drying them to obtain the conductive powder.

[0015] In one or more embodiments, in step a, copper powder is added to a solution containing a reducing agent, stirred, separated to obtain a solid, and the solid is dried to obtain the copper powder with the oxide layer removed; in the solution containing the reducing agent, the concentration of the reducing agent is 5-15 mol / L.

[0016] In one or more embodiments, in step a, the reducing agent is selected from one or more of formic acid, formaldehyde, vitamin C, sodium borate and potassium borate.

[0017] In one or more embodiments, in step b, the concentration of the surfactant in the aqueous solution containing the surfactant is 0.01-0.05 mol / L.

[0018] In one or more embodiments, in step b, 350-450 g of copper powder with oxide layer removed is added to each liter of aqueous solution containing a surfactant.

[0019] In one or more embodiments, in step b, the stirring is performed at 20-50°C.

[0020] In one or more embodiments, in step b, the stirring is ultrasonic stirring.

[0021] In one or more embodiments, in step b, the drying temperature is 50-80°C.

[0022] In one or more embodiments, in step b, the drying time is 4-24 hours.

[0023] In one or more embodiments, in step c, the concentration of graphene in the graphene-containing liquid is 1-5 mg / mL.

[0024] In one or more embodiments, in step c, 350-450 g of surfactant-modified copper powder is added to each liter of the liquid containing graphene.

[0025] In one or more embodiments, in step c, the stirring is ultrasonic stirring.

[0026] In one or more embodiments, in step c, the drying temperature is 50-80°C.

[0027] In one or more embodiments, in step c, the drying time is 4-24 hours.

[0028] In one or more embodiments, in step c, the mixture is allowed to stand for 5-20 minutes.

[0029] According to a third aspect of the present invention, a conductive paste is provided, wherein the conductive paste comprises the conductive powder according to the first aspect of the present invention.

[0030] In one or more embodiments, the conductive paste further includes an auxiliary agent, a solvent, and a binder.

[0031] In one or more embodiments, the auxiliary agent is selected from one or more of a dispersant, a silane coupling agent and a defoaming agent.

[0032] In one or more embodiments, the solvent is selected from one or more of diethyl adipate, diethylene glycol butyl ether acetate and 1,4-butyrolactone.

[0033] In one or more embodiments, the binder is selected from one or more of polyester resins and acrylic resins.

[0034] In one or more embodiments, the conductive paste includes 50-90 wt % of the conductive powder, 0.1-20 wt % of the solvent, 0.1-10 wt % of the auxiliary agent, and 0.1-30 wt % of the binder.

[0035] The fourth aspect of the present invention provides a method for preparing the conductive paste described in the third aspect of the present invention, the method comprising the step of uniformly mixing the conductive powder with the remaining raw materials of the conductive paste.

[0036] The fifth aspect of the present invention provides a conductive material prepared using the conductive paste described in the third aspect of the present invention.

[0037] A sixth aspect of the present invention provides a method for preparing the conductive material described in the fifth aspect, the method comprising the step of heating and curing the conductive paste.

[0038] The present invention has the following beneficial effects: The present invention provides an antioxidant low-temperature conductive paste and a preparation method thereof, and the present invention also provides a conductive material obtained by curing the conductive paste. The conductive paste of the present invention is more stable than the traditional conductive copper paste. On the one hand, by modifying the surface of the copper powder, graphene is more evenly coated on the surface of the copper powder particles, so that continuous contact is formed between the conductive particles to increase the contact area, thereby increasing the conductivity of the entire conductive material; on the other hand, since the surface of the copper powder in the conductive paste is coated with graphene, the copper powder can be prevented from being oxidized, and its sintering and curing conditions can be changed from a protective atmosphere to an air atmosphere, further reducing costs, thereby expanding the application range of the conductive paste. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 This is the SEM morphology of the conductive powder prepared in Example 2 of the present invention. DETAILED DESCRIPTION

[0040] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.

[0041] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.

[0042] Herein, “comprising”, “including”, “containing” and similar terms encompass the meanings of “consisting essentially of” and “consisting of”. For example, when “A comprises B and C” is disclosed herein, “A consists essentially of B and C” and “A consists of B and C” should be deemed to be disclosed herein.

[0043] In this document, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible sub-ranges and individual values ​​within the range (including integers and fractions).

[0044] In this document, unless otherwise specified, percentage refers to mass percentage and ratio refers to mass ratio.

[0045] Herein, when describing embodiments or examples, it should be understood that they are not used to limit the present invention to these embodiments or examples. On the contrary, all substitutes, improvements and equivalents of the methods and materials described in the present invention can be included in the scope limited by the claims.

[0046] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.

[0047] The inventors have found that the use of graphene-coated copper powder to prepare conductive paste can expand the application range of the conductive paste. Specifically, by modifying the surface of the copper powder, the graphene can be more evenly coated on the surface of the copper powder particles, so that the particles inside the conductive paste form continuous contact and the contact area of ​​the conductive particles becomes larger, thereby increasing the conductivity of the entire conductive material; on the other hand, since the surface of the copper powder in the conductive paste is coated with graphene, the copper powder can be prevented from being oxidized, and its sintering and curing conditions can be changed from a protective atmosphere to an air atmosphere, further reducing the curing cost, thereby expanding the application range of the conductive paste.

[0048] The invention provides a conductive powder, which comprises copper powder modified by a surfactant and a graphene coating layer coated on the surface of the copper powder modified by the surfactant.

[0049] In some embodiments, the conductive powder of the present invention is graphene-coated copper powder particles.

[0050] The copper powder may be micro-nano copper powder of any shape, such as sphere, flake, dendrite, nanowire, irregular particle, etc. In some embodiments, the average particle size of the copper powder is ≤8 μm, preferably ≤5 μm, such as 1-5 μm, 2-5 μm.

[0051] In some embodiments, the surfactant is selected from one or more of disodium ethylenediaminetetraacetate, sodium dodecyl sulfate, cetyltrimethylammonium bromide and sodium dodecylbenzenesulfonate, preferably cetyltrimethylammonium bromide. In the copper powder modified by the surfactant, the non-polar end of the surfactant is adsorbed on the copper powder.

[0052] In some embodiments, the coverage of the graphene coating layer on the surface of the surfactant-modified copper powder is 90-100%, such as 95%, 98%.

[0053] In some embodiments, the sheet diameter of graphene is 1-3 μm, such as 1-2 μm, 2-3 μm.

[0054] In some embodiments, the graphene is a single layer or two, three, four or five layers.

[0055] In some embodiments, the thickness of the graphene coating is less than 10 nm, for example, 1 nm, 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, 10 nm.

[0056] In some embodiments, in the conductive powder, the mass fraction of the graphene coating layer is 1-2%, for example, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, preferably 1.3-1.7%. The conductive powder of the present invention contains a very small amount of surfactant, and the content of the surfactant in the conductive powder cannot be measured using a conventional laboratory electronic balance. Therefore, the mass of the conductive powder can be approximately regarded as consisting of two parts: copper powder and graphene coating layer.

[0057] The present invention also provides a method for preparing the conductive powder of the present invention, the method comprising the steps of: a. treating the copper powder with a reducing agent to obtain the copper powder with the oxide layer removed; b. adding the copper powder with the oxide layer removed into an aqueous solution containing a surfactant, stirring, separating to obtain a solid, and drying the solid to obtain a copper powder modified by a surfactant; c. Adding the copper powder modified by the surfactant into the liquid containing graphene, stirring until floccules appear and then letting the mixture stand, separating the floccules and drying them to obtain a conductive powder.

[0058] In some embodiments, copper powder, surfactant, and graphene are as defined in any embodiment herein.

[0059] In step a, copper powder is added to a solution containing a reducing agent, stirred, separated to obtain a solid, and the solid is dried to obtain copper powder with the oxide layer removed. In the solution containing a reducing agent, the concentration of the reducing agent may be 5-15 mol / L, for example, 7-10 mol / L or 10-13 mol / L. Preferably, the drying is vacuum drying, and the drying temperature is preferably 50-100°C, for example, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C. Preferably, the stirring is ultrasonic stirring, and the ultrasonic stirring is preferably performed for 10-60 min, for example, 30-40 min.

[0060] In step a, the reducing agent is selected from one or more of formic acid, formaldehyde, vitamin C, sodium borate and potassium borate, preferably formic acid.

[0061] In step b, the copper powder is modified with a surfactant (such as CTAB) by an electrostatic self-assembly method. In the aqueous solution containing the surfactant, the concentration of the surfactant is 0.01-0.05 mol / L, such as 0.01 mol / L, 0.02 mol / L, 0.03 mol / L, 0.04 mol / L, 0.05 mol / L.

[0062] In step b, 350-450 g of copper powder with the oxide layer removed is added to each liter of the aqueous solution containing the surfactant, for example, 360 g, 380 g, 400 g, 420 g, or 440 g.

[0063] In step b, stirring is performed at 20-50° C., such as 25° C., 30° C., 35° C., 40° C. In step b, stirring is ultrasonic stirring, and ultrasonic stirring is preferably performed for 10-60 min, such as 20 min, 30 min, 40 min, 50 min.

[0064] In step b, the drying temperature is 50-80°C, for example, 50°C, 60°C, 70°C, 80°C.

[0065] In step b, the drying time is 4-24 h, for example, 5 h, 8 h, 10 h, 12 h, 15 h, 18 h, 24 h, 30 h.

[0066] In step c, the concentration of graphene in the liquid containing graphene is 1-5 mg / mL, for example, 1 mg / mL, 2 mg / mL, 3 mg / mL, 4 mg / mL, 5 mg / mL.

[0067] In step c, 350-450 g of copper powder modified by a surfactant is added to each liter of liquid containing graphene, for example, 350 g, 360 g, 370 g, 380 g, 390 g, 400 g, 403 g, 405 g, 406 g, 410 g, 420 g, and 430 g.

[0068] In step c, the stirring is ultrasonic stirring, and the ultrasonic stirring is preferably performed for 24-72 h, for example, 24 h, 30 h, 35 h, 42 h, 48 h, 54 h, 60 h, 64 h, 70 h.

[0069] In step c, the drying temperature is 50-80°C, for example, 50°C, 60°C, 70°C, 80°C.

[0070] In step c, the drying time is 4-24 h, for example, 6 h, 8 h, 10 h, 15 h, 18 h, 20 h, 22 h.

[0071] In step c, the mixture is allowed to stand for 5-20 min, for example, 5 min, 8 min, 10 min, 15 min, 18 min, 20 min, preferably until the preparation system of step c is separated into layers.

[0072] The present invention also provides a conductive paste, which includes the conductive powder of the present invention. Based on the total weight of the conductive paste, the content of the conductive powder in the conductive paste of the present invention is 50-90wt%, such as 60wt%, 65wt%, 70wt%, 75wt%, 80wt%, 85wt%.

[0073] The conductive paste of the present invention further comprises an auxiliary agent, a solvent and a binder.

[0074] The additives suitable for the conductive paste of the present invention include, but are not limited to, toughening agents, accelerators, coupling agents, rheological additives, anti-settling agents, defoaming agents, antioxidants, etc. Based on the total mass of the conductive paste, the content of the additives in the conductive paste of the present invention is 0.1-10wt%, for example, 0.2wt%, 0.5wt%, 0.8wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 4wt%, 4.6wt%, 5wt%, 10wt%.

[0075] The accelerator is usually a curing accelerator. The accelerator suitable for the present invention can be an imidazole curing accelerator. Examples of imidazole curing accelerators include 2-methylimidazole, 1-methylimidazole, 2-ethyl-4-methylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 2-undecylimidazole, 2-phenylimidazole and 2-phenyl-4-methylimidazole. In some embodiments, the accelerator in the conductive paste of the present invention includes one or more selected from 2-ethyl-4-methylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole and 2-phenyl-4-methylimidazole. When the conductive paste includes the accelerator, the content of the accelerator in the conductive paste of the present invention can be 0.05~1wt%, such as 0.08wt%, 0.1wt%, 0.2wt%, 0.5wt%, based on the total mass of the conductive paste.

[0076] The coupling agent suitable for the present invention can be one or more selected from silane coupling agents, titanate coupling agents, and aluminate coupling agents. In some embodiments, the coupling agent in the conductive paste of the present invention comprises a silane coupling agent. Examples of silane coupling agents include A150, KH-560, KH-570, and KBM-603. When the conductive paste comprises a coupling agent, the content of the coupling agent in the conductive paste of the present invention can be 0.01-1wt%, such as 0.02wt%, 0.05wt%, 0.1wt%, and 0.5wt%, based on the total mass of the conductive paste.

[0077] Rheological additives suitable for the present invention may include one or more selected from dispersants, thixotropic agents and leveling agents. In some embodiments, the rheological additives in the conductive paste of the present invention include dispersants and / or thixotropic agents. Examples of dispersants include Silok-7423, Silok-7421, Silok-7455H, Silok-7631, Silok-7096, Silok-7160, BYK-111, BYK204, BYK-2155, BYK-2008, BYK-170, BYK-2025, BYK-220S, BYK-106, BYK-370, BYK-388, Deqian D9850, Deqian 983, Deqian 904S, Deqian 910, Deqian 912, Deqian 929, DARVANC-N and Shin-Etsu 4803. Examples of thixotropic agents include polyethylene wax, organic bentonite, castor oil, hydrogenated castor oil and fumed silica. When the conductive paste includes a rheological additive, the content of the rheological additive in the conductive paste of the present invention may be 0.01-10wt%, such as 0.1wt%, 0.15wt%, 0.17wt%, 0.25wt%, 0.35wt%, 0.5wt%, 1 wt%, 1.5wt%, 2 wt%, 3 wt%, 4 wt%, 5 wt%, 6 wt%, 7 wt%, 8 wt%, 9 wt%, 10 wt%, based on the total mass of the conductive paste. When the rheological additive includes a dispersant and a thixotropic agent, the mass ratio of the dispersant to the thixotropic agent may be 1:1 to 1:3.

[0078] In some embodiments, the auxiliary agent is selected from one or more of a dispersant (eg, BYK204), a silane coupling agent (eg, A150), and a defoaming agent (eg, BYK057), preferably a dispersant.

[0079] The solvent suitable for the conductive paste of the present invention can be one or more selected from hydrocarbon solvents, ester solvents, ether solvents, alcohol solvents, ketone solvents and amide solvents, for example, it can include one or more selected from naphtha, dimethylformamide, dimethylacetamide, N-methyl-2-pyrrolidone, DBE, ethylene glycol ethyl ether acetate, ethylene glycol butyl ether acetate, diethylene glycol butyl ether acetate, dimethyl succinate, dimethyl glutarate, dipropylene glycol methyl ether, dipropylene glycol butyl ether, diacetone alcohol, 3-methoxy butyl acetate, 3-methoxy butyl propionate, propylene carbonate, butyl acetate, diethylene glycol diacetate. In some embodiments, the solvent in the conductive paste of the present invention is selected from one or more of diethyl adipate, diethylene glycol butyl ether acetate and 1, 4-butyrolactone, preferably diethylene glycol butyl ether acetate.

[0080] In the conductive paste of the present invention, the content of the solvent is 0.1-20 wt %, for example, 2 wt %, 2.5 wt %, 3 wt %, 4 wt %, 4.6 wt %, 5 wt %, or 10 wt %, based on the total mass of the conductive paste.

[0081] In some embodiments, the binder is selected from one or more of polyester resin and acrylic resin, preferably polyester resin (BX1000) and acrylic resin (BR117). Based on the total weight of the conductive paste, the content of the binder in the conductive paste of the present invention may be 0.1-30 wt%, for example, 1 wt%, 2 wt%, 3 wt%, 4 wt%, 5 wt%, 10 wt%, 15 wt%, 20 wt%, 25 wt%.

[0082] In some embodiments, the conductive paste comprises 50-90wt% conductive powder, 0.1-20wt% solvent, 0.1-10wt% auxiliary agent and 0.1-30wt% binder. Preferably, the conductive paste comprises 85-90wt% conductive powder, 2-6wt% solvent, 3-8wt% auxiliary agent and 1-5wt% binder.

[0083] The present invention also provides a method for preparing the conductive paste of the present invention, the method comprising the steps of: 1. Provide the conductive powder of the present invention; 2. Mix the conductive powder and other raw materials of the conductive paste (for example, one or more or all of the self-reinforcement agent, solvent and binder) to prepare the conductive paste.

[0084] In some embodiments, the present invention provides a method for preparing the conductive paste of the present invention, the method comprising the step of uniformly mixing the conductive powder of the present invention with the remaining raw materials of the conductive paste (for example, one or more or all selected from the group consisting of an agent, a solvent and a binder).

[0085] The conductive powder, additive, solvent and binder are as defined in any embodiment of this invention.

[0086] In some embodiments, in step 2, 50-90wt% of conductive powder, 0.1-20wt% of solvent, 0.1-10wt% of auxiliary agent and 0.1-30wt% of binder are mixed. Preferably, in step 2, 85-90wt% of conductive powder, 2-6wt% of solvent, 3-8wt% of auxiliary agent and 1-5wt% of binder are mixed.

[0087] In step 2, the mixing can be carried out by a conventional mixing method in the art, for example, stirring and grinding. In some embodiments, the conductive powder, additive, solvent and binder are mixed by stirring and grinding. Preferably, the stirring is 1-60 minutes, for example, 3-30 minutes, 5-20 minutes. Preferably, the stirring is carried out by a centrifuge. Preferably, the grinding is carried out by a three-roll mill. Preferably, the mixing is carried out by stirring first and then grinding.

[0088] The present invention also provides a conductive material prepared using the conductive paste of the present invention. The conductive material of the present invention has a graphene conductive film structure on its surface and / or inside. The graphene in the graphene conductive film structure can be a single layer or multiple layers (two layers, three layers, four layers or five layers).

[0089] The conductive material of the present invention can be prepared by printing a conductive paste on a substrate, drying and curing. The conductive material can be present on the substrate in the form of a pattern. The substrate can be a flexible substrate, such as a PI film and a PEEK film.

[0090] The present invention also provides a method for preparing the conductive material of the present invention, the method comprising the step of heating and curing the conductive paste of the present invention.

[0091] In some embodiments, the temperature of heat curing is 150-300°C, such as 160°C, 180°C, 200°C, 220°C, 250°C, 280°C, 300°C, preferably 200-250°C.

[0092] In some embodiments, the heating curing time is 20-60 min, such as 20 min, 30 min, 40 min, 50 min, 60 min, preferably 30-40 min.

[0093] The present invention also provides an electronic device, which includes the conductive material of the present invention. Preferably, the electronic device can be selected from a touch screen, an LED, a solar cell, a sensor, a printed circuit board, an RFID, etc. In some embodiments, the electronic device of the present invention may include a substrate and the conductive material of the present invention present on the substrate.

[0094] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples without specifying specific conditions are usually based on conventional conditions or the conditions recommended by the manufacturer. Unless otherwise stated, percentages and parts are calculated by weight.

[0095] In this article, the calculation method of graphene coverage is as follows: 1. Test the specific surface areas of graphene, pure copper powder before coating, and copper powder coated with graphene coating layer; 2. Subtract the specific surface area of ​​copper powder before coating from the specific surface area of ​​copper powder after coating to obtain the difference; 3. The ratio of the difference to the specific surface area of ​​graphene is the graphene coverage.

[0096] In this paper, the thickness of the graphene coating layer is calculated as follows: 1. Test the specific surface area and average particle size of the copper powder before coating and after coating with the graphene coating layer; 2. Assuming that the copper powder before coating and the copper powder after coating with the graphene coating layer are both regular spheres, the surface area of ​​the sphere is calculated by the formula S=4πR 2 , calculate the radius difference of the copper powder sphere before and after coating, which is the graphene thickness.

[0097] Herein, the specific surface area is measured by a specific surface area meter.

[0098] In this paper, the average particle size is measured by a laser particle size analyzer.

[0099] In this paper, the diameter of graphene sheets was measured by transmission electron microscopy.

[0100] The specific surface area of ​​the uncoated pure copper powder used in the examples and comparative examples herein is 0.7075 m 2 / g.

[0101] The specific surface area of ​​the graphene used in the examples and comparative examples herein is 36.9 m 2 / g.

[0102] Example 1: Preparation of conductive material using slurry containing graphene-coated copper powder

[0103] 1. Preparation of graphene-coated copper powder

[0104] a. Take thin copper powder with an average particle size of 2-5μm; take graphene with a purity of ≥99% and a particle size range of 1-3μm. Add the copper powder to 10mol / L formic acid, stir ultrasonically for 30min, then centrifuge at 2000rpm to obtain a precipitate, wash the precipitate three times with deionized water, and dry it in a vacuum oven at 70℃.

[0105] b. Weigh 1 g of CTAB powder and 100 mL of deionized water, heat and stir until the powder is dissolved, then add 40 g of copper powder, and then stir under ultrasonic vibration for 30 min, filter, and vacuum dry for 8 h at 60 °C to obtain CTAB-modified copper powder.

[0106] c. Take 2 mg / mL (100 mL) of graphene solution, add all the modified copper powder prepared in step b to the graphene solution, stir ultrasonically for 48 hours, continue stirring until flocculent substances appear, let stand for about 10 minutes, and stratify. Filter the flocculent substances under vacuum and dry them for 8 hours at 60 °C to obtain 40.62g of graphene-coated copper powder. The coverage of graphene is 95%, and the thickness of the graphene coating layer is 8nm.

[0107] 2. Preparation of Conductive Materials

[0108] a. Weigh the following materials according to the following mass percentages: 85% of the graphene-coated copper powder prepared in step 1, 5% of BX1000 polyester resin, 1% of BR117 acrylic resin, 8% of diethylene glycol butyl ether acetate, and 1% of BYK204 dispersant.

[0109] b. The materials in a are uniformly mixed according to the proportion, stirred in a centrifuge for 5-10 minutes, and ground in a three-roll mill for 8 times to obtain a low-temperature conductive copper slurry.

[0110] c. The low-temperature conductive copper paste obtained in step b is cured (200°C / 30min) to obtain a low-temperature anti-oxidation conductive material 1#.

[0111] Example 2: Preparation of conductive material using slurry containing graphene-coated copper powder

[0112] 1. Preparation of graphene-coated copper powder

[0113] a. Take spherical copper powder with an average particle size of 2-5μm; take graphene with a purity of ≥99% and a flake size range of 1-3μm. Add the copper powder to 10mol / L formic acid, stir ultrasonically for 30min, then centrifuge at 2000rpm to obtain a precipitate, wash the precipitate three times with deionized water, and dry it in a vacuum oven at 70℃.

[0114] b. Weigh 1 g of CTAB powder and 100 mL of deionized water, heat and stir until the powder is dissolved, then add 40 g of copper powder, and then stir under ultrasonic vibration for 30 min, filter, and vacuum dry for 8 h at 60 °C to obtain 40.54 g of CTAB-modified copper powder.

[0115] c. Take 2 mg / mL (100 mL) of graphene solution, add all the modified copper powder prepared in step b to the graphene solution, stir ultrasonically for 48 hours, continue stirring until flocculent substances appear, let stand for about 10 minutes, and stratify. Filter the flocculent substances under vacuum and dry them for 8 hours at 60 °C to obtain 40.54g of graphene-coated copper powder. The coverage of graphene is 92%, and the thickness of the graphene coating layer is 10nm.

[0116] 2. Preparation of Conductive Materials

[0117] a. Weigh the following materials according to the following mass percentages: 85% of the graphene-coated copper powder prepared in step 1, 5% of BX1000 polyester resin, 1% of BR117 acrylic resin, 8% of diethylene glycol butyl ether acetate, and 1% of BYK204 dispersant.

[0118] b. The materials in a are uniformly mixed according to the proportion, stirred in a centrifuge for 5-10 minutes, and ground in a three-roll mill for 8 times to obtain a low-temperature conductive copper slurry.

[0119] c. Curing the low-temperature conductive copper paste obtained in step b (200° C. / 30 min) to obtain low-temperature anti-oxidation conductive material 2#.

[0120] Comparative Example 1: Preparation of a conductive material using a slurry containing copper powder not coated with graphene

[0121] 1. Preparation of copper powder without graphene

[0122] Take thin flake copper powder with an average particle size of 2-5 μm, add the copper powder to 10 mol / L formic acid, and stir ultrasonically for 30 minutes to remove the oxide layer on the copper surface. Then centrifuge at 2000 rpm to obtain a precipitate, wash the precipitate three times with deionized water, and dry it in a vacuum oven at 70°C.

[0123] 2. Preparation of Conductive Materials

[0124] a. Weigh the materials according to the following mass percentages: copper powder 85%, BX1000 polyester resin 5%, BR117 acrylic resin 1%, diethylene glycol butyl ether acetate 8%, BYK204 dispersant 1%.

[0125] b. The materials in a are uniformly mixed according to the proportion, stirred in a centrifuge for 5-10 minutes, and ground in a three-roll mill for 8 times to obtain a low-temperature conductive copper slurry.

[0126] c. The low-temperature conductive copper paste prepared in step b was cured (200°C / 30min) to obtain comparative low-temperature conductive material 1#.

[0127] Comparative Example 2: Preparation of a conductive material using a slurry containing copper powder not coated with graphene

[0128] 1. Preparation of copper powder without graphene

[0129] Take spherical copper powder with an average particle size of 2-5 μm. Add the copper powder to 10 mol / L formic acid and stir ultrasonically for 30 minutes to remove the oxide layer on the copper surface. Then centrifuge at 2000 rpm to obtain a precipitate, wash the precipitate three times with deionized water, and dry it in a vacuum oven at 70°C.

[0130] 2. Preparation of Conductive Materials

[0131] a. Weigh the materials according to the following mass percentages: copper powder 85%, BX1000 polyester resin 5%, BR117 acrylic resin 1%, diethylene glycol butyl ether acetate 8%, BYK204 dispersant 1%.

[0132] b. The materials in a are uniformly mixed according to the proportion, stirred in a centrifuge for 5-10 minutes, and ground in a three-roll mill for 8 times to obtain a low-temperature conductive copper slurry.

[0133] c. The low-temperature conductive copper paste prepared in step b was cured (200°C / 30min) to obtain comparative low-temperature conductive material 2#.

[0134] Test Case

[0135] The performance of the conductive materials prepared in Examples 1-2 and Comparative Examples 1-2 was tested.

[0136] The resistance was tested by a Hioki M3545 resistance meter with a line length of 100 mm, a line width of 1 mm, and a film thickness of 12 μm, and the resistivity was then calculated according to the formula.

[0137] The oxidation resistance of copper powder was tested by TG, and the weight gain of copper powder was measured under the condition of keeping the temperature in air at 200°C for 1 hour.

[0138] The results are shown in Table 1: Table 1

[0139] It can be clearly concluded from the test data that the copper paste (low-temperature conductive copper paste prepared in Example 1-2) prepared by using graphene-coated copper powder (conductive powder of the present invention) has a resistivity significantly lower than that of Comparative Example 1-2, that is, the conductive performance is significantly better than that of the Comparative Example; the weight gain of the low-temperature conductive copper paste prepared in Example 1-2 is much lower than that of the copper paste in Comparative Example 1-2, indicating that the coating of the copper powder by graphene has a good protective effect, thereby enhancing the antioxidant ability of the copper powder, thereby showing good conductivity and stability.

[0140] The above are only some embodiments of the present invention. For those skilled in the art, several modifications and improvements are possible without departing from the creative concept of the present invention, and these all belong to the protection scope of the present invention.

Claims

1. A conductive powder, characterized in that: The conductive powder comprises copper powder modified by a surfactant and a graphene coating layer coated on the surface of the copper powder modified by the surfactant.

2. The conductive powder according to claim 1, characterized in that: The conductive powder has one or more of the following characteristics: The average particle size of the copper powder is ≤8 μm; The surfactant is selected from one or more of disodium ethylenediaminetetraacetate, sodium dodecyl sulfate, cetyltrimethylammonium bromide and sodium dodecylbenzene sulfonate; The graphene sheet diameter is 1-3 μm; The thickness of the graphene coating layer is less than 10 nm; The coverage rate of the graphene coating layer on the surface of the copper powder modified by the surfactant is 90-100%; In the conductive powder, the mass fraction of the graphene coating layer is 1-2%.

3. A method for preparing the conductive powder according to claim 1 or 2, characterized in that: The method comprises the steps of: a. treating the copper powder with a reducing agent to obtain the copper powder with the oxide layer removed; b. adding the copper powder with the oxide layer removed into an aqueous solution containing a surfactant, stirring, separating to obtain a solid, and drying the solid to obtain the copper powder modified by the surfactant; c. Adding the copper powder modified by the surfactant into the liquid containing graphene, stirring until floccules appear, and then standing to separate the floccules and drying them to obtain the conductive powder.

4. The method according to claim 3, characterized in that The method has one or more of the following features: In step a, copper powder is added to a solution containing a reducing agent, stirred, separated to obtain a solid, and the solid is dried to obtain the copper powder with the oxide layer removed; in the solution containing the reducing agent, the concentration of the reducing agent is 5-15 mol / L; In step a, the reducing agent is selected from one or more of formic acid, formaldehyde, vitamin C, sodium borate and potassium borate; In step b, in the aqueous solution containing a surfactant, the concentration of the surfactant is 0.01-0.05 mol / L; In step b, 350-450 g of copper powder with the oxide layer removed is added to each liter of the aqueous solution containing the surfactant; In step b, the stirring is carried out at 20-50°C; In step b, the stirring is ultrasonic stirring; In step b, the drying temperature is 50-80°C; In step b, the drying time is 4-24h; In step c, the concentration of graphene in the liquid containing graphene is 1-5 mg / mL; In step c, 350-450 g of copper powder modified with a surfactant is added to each liter of liquid containing graphene; In step c, the stirring is ultrasonic stirring; In step c, the drying temperature is 50-80°C; In step c, the drying time is 4-24 hours; In step c, let stand for 5-20 minutes.

5. A conductive paste, characterized in that: The conductive paste comprises the conductive powder according to claim 1 or 2.

6. The conductive paste according to claim 5, characterized in that: The conductive paste further comprises an auxiliary agent, a solvent and a binder.

7. The conductive paste according to claim 6, characterized in that: The conductive paste has one or more of the following characteristics: The auxiliary agent is selected from one or more of a dispersant, a silane coupling agent and a defoaming agent; The solvent is selected from one or more of diethyl adipate, diethylene glycol butyl ether acetate and 1,4-butyrolactone; The binder is selected from one or more of polyester resin and acrylic resin; The conductive paste includes 50-90 wt % of the conductive powder, 0.1-20 wt % of the solvent, 0.1-10 wt % of the auxiliary agent and 0.1-30 wt % of the binder.

8. A method for preparing the conductive paste according to any one of claims 5 to 7, characterized in that: The method comprises the step of uniformly mixing the conductive powder with other raw materials of the conductive paste.

9. A conductive material prepared using the conductive paste according to any one of claims 5 to 7.

10. A method for preparing the conductive material according to claim 9, characterized in that: The method comprises the step of heating and curing the conductive paste.

Citation Information

Patent Citations

  • Uniform spherical graphene / single crystal copper composite powder and preparation method thereof

    CN107414070A

  • Copper plating nanoparticle graphene conducting ink and preparation method thereof

    CN108753044A

  • Graphene composite nano-copper conductive ink composition and preparation method thereof

    CN108912847A

  • Preparation process and packaging application of graphene-coated nano-copper slurry

    CN112185623A

  • Method for preparing graphene on surface of copper powder

    CN114572971A

Cited By

  • Preparation method of graphene coated copper powder

    CN120940641A

  • Graphene coated copper powder thermosetting conductive adhesive film and preparation method thereof

    CN122060438A